Ischemic heart disease awareness in Egypt's aging population: findings from a national cross-sectional study - Mohamed Saad Rakab; Mohamed Baklola; Basel Hatem Elsalakawi; Moaz Mohamed Zaki; Mohamed Elhusseini Elsaeidi; Hossam Fouad; Belal Walid; Abdelrahman Elbaz; Ali Emara; Abdelrahman Sherif Ghanem; Nada Mohammed Radwan; Ahmed Reda Abdelmeguid; et al. (The Egyptian Heart Journal)
Abstract Background Ischemic heart disease (IHD) remains a leading cause of mortality among the elderly population, particularly in low- and middle-income countries like Egypt, where public health infrastructure may struggle to meet the needs of a growing aging population. Awareness of the risk factors and warning signs associated with IHD is critical for early detection and intervention. This study aimed to evaluate the level of awareness and knowledge regarding IHD risk factors and warning signs among elderly individuals in Egypt, focusing on differences between urban and rural populations. Results Among 595 participants aged 60 years and above, only 18.7% demonstrated good knowledge of IHD risk factors, whereas 47.2% were categorized as having poor knowledge. In terms of warning signs, 7.2% exhibited good awareness, while 47.9% showed poor awareness. Overall, more than half (51.8%) of the participants were found to have poor knowledge of IHD, and just 15.1% had good overall awareness of both risk factors and warning signs. Urban participants exhibited significantly higher knowledge compared to rural participants (p < 0.05). Educational attainment was a strong predictor of knowledge, with participants holding postgraduate degrees scoring the highest. Economic status also influenced awareness, with those in the excellent category demonstrating significantly higher knowledge (p < 0.05). Occupation had a notable impact, with engineers exhibiting the highest levels of awareness and farmers the lowest. Gender, however, was not a significant factor, with males and females showing similar levels of awareness. Conclusions The study reveals a significant knowledge gap concerning IHD risk factors and warning signs among Egypt’s elderly population, particularly in rural areas and among individuals with lower levels of education and economic status. This gap underscores the need for targeted public health campaigns and interventions, particularly in rural regions, to raise awareness and reduce the burden of IHD among Egypt's elderly. Enhanced education and community-based programs could be effective in mitigating the risks associated with poor awareness of IHD.